2019
DOI: 10.18203/2320-6012.ijrms20191675
|View full text |Cite
|
Sign up to set email alerts
|

A study of prevalence of peripheral arterial disease in type 2 diabetes mellitus using ankle-brachial index and its correlation with coronary artery disease and its risk factors

Abstract: A reliable diagnosis of PAD can be made using the anklebrachial index (ABI). This simple, painless and highly reproducible test can be performed in a physician's office and requires only a blood pressure apparatus and a handheld, continuous-wave doppler probe. ABSTRACTBackground: Peripheral arterial disease (PAD) is one of the macrovascular complications of type 2 diabetes mellitus (T2DM). There is significant difference in the reported prevalence of PAD and its associated risk factors between Indian and Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In our study, the prevalence of hypertension in ABI +VE group was 67.85% and 41.66% in the ABI −VE group, showing a statistically significant difference. Similarly, Sharma et al [7] found that in ABI +VE group, mean systolic blood pressure and mean diastolic blood pressure were significantly higher (P < 0.05) as compared to the ABI −VE group.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In our study, the prevalence of hypertension in ABI +VE group was 67.85% and 41.66% in the ABI −VE group, showing a statistically significant difference. Similarly, Sharma et al [7] found that in ABI +VE group, mean systolic blood pressure and mean diastolic blood pressure were significantly higher (P < 0.05) as compared to the ABI −VE group.…”
Section: Discussionmentioning
confidence: 73%
“…In our study, history of smoking in ABI +VE group was 71.42% and 38.88% in the ABI −VE group, showing a statistically significant difference. Similarly, Sharma et al [7] found that history of smoking was higher in the ABI +VE group (33.3%) as compared to ABI −VE group (11.8%).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations